Comparison of the torsional fretting behavior of three porous titanium coatings for biomedical applications. (December 2015) - Quan, Huixin; Gao, Shanshan; Zhu, Minhao; Yu, Haiyang
Abstract: This research evaluated the torsional fretting wear proprieties of three porous bio-coatings modified with anodic oxidation, acid–base treatment, and alkali–heat treatment. Torsional fretting wear tests were carried out under a ball-on-flat contact configuration. Torsional fretting wear mechanisms were investigated by a combination of scanning electron microscope observations, energy dispersive X-ray analysis and X-ray diffraction analysis. Results showed that the torsional fretting wear resistance of anodic oxidation coating was better than that of acid–base coating and alkali–heat coating. Adhesive wear was the main damage mechanism of the three porous titanium coatings in partial slip regime. The combination of abrasive wear, delamination, and material transfer was the main wear mechanism of mixed and gross slip regimes. Highlights: AO coating had better wear resistance to torsional fretting than AH and AB coating. Adhesive wear was damage mechanism during partial slip regime. Abrasive wear, delamination wear, and material transfer were wear mechanism of mixed and gross slip regimes.